CONTEMPORARY ASPECTS OF PREGNANCY AND DELIVERY MANAGEMENT IN WOMEN WITH EPILEPSY - Kosimkhojieva F.T., Zufarova Sh.A., Khodjieva D.T. (Central Asian Journal of Medicine, 2025)
Management of women in labor with epilepsy is one of the most pressing and little-studied problems of motherhood and childhood. The prevalence of epilepsy in the general population is approximately 1%, with 25–40% of patients being women of reproductive age. Insufficient knowledge of the comorbidity of a condition at the intersection of neurology and obstetrics and gynecology often causes many unfounded fears or, conversely, remains without due attention.